2016
DOI: 10.14235/bs.2016.618
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Risk Factors of Low Back Pain in Students Studying at a Health University

Abstract: Objective: The aim of this study was to determine the incidence, severity, and risk factors of low back pain in students studying at a health university. Methods: The study was conducted on students of dentistry, pharmacy, health sciences, and medicine faculties of Bezmialem Vakif University. The data were gathered using a 35-question survey. Five hundred and twenty students completed the questionnaire. Four hundred and seventyone (90.57%) of them answered pain-specific questions. Visual analogue scale was use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 18 publications
6
24
0
Order By: Relevance
“…In contrast, in studies where a link between cigarette smoking and LBP was not found ( Algarni et al, 2017 ; Aggarwal et al, 2013 ; AlShayhan & Saadeddin, 2018 ; Smith et al, 2005 ; Haroon et al, 2018 ) prevalence of smoking was less than 10% in both students with and without LBP. Besides that, the lack of association between cigarette smoking and LBP in the majority of studies can be attributed to young age of medical students in whom LBP has not occurred yet: while in our study and in the study by Hafeez et al (2013) , where an association between cigarette smoking and LBP was found, the average age of participants was 22 and over, in studies where this association was not found, the average age of students was less than 22 ( Algarni et al, 2017 ; Aggarwal et al, 2013 ; AlShayhan & Saadeddin, 2018 ; Smith et al, 2005 ; Haroon et al, 2018 ; Yucel & Torun, 2016 ). Also, study participants were medical students in whom education is encouraging them to give up smoking.…”
Section: Discussionsupporting
confidence: 44%
See 3 more Smart Citations
“…In contrast, in studies where a link between cigarette smoking and LBP was not found ( Algarni et al, 2017 ; Aggarwal et al, 2013 ; AlShayhan & Saadeddin, 2018 ; Smith et al, 2005 ; Haroon et al, 2018 ) prevalence of smoking was less than 10% in both students with and without LBP. Besides that, the lack of association between cigarette smoking and LBP in the majority of studies can be attributed to young age of medical students in whom LBP has not occurred yet: while in our study and in the study by Hafeez et al (2013) , where an association between cigarette smoking and LBP was found, the average age of participants was 22 and over, in studies where this association was not found, the average age of students was less than 22 ( Algarni et al, 2017 ; Aggarwal et al, 2013 ; AlShayhan & Saadeddin, 2018 ; Smith et al, 2005 ; Haroon et al, 2018 ; Yucel & Torun, 2016 ). Also, study participants were medical students in whom education is encouraging them to give up smoking.…”
Section: Discussionsupporting
confidence: 44%
“…Also, some authors reported point prevalence of 13.0% among medical students at one university in Pakistan ( Hafeez et al, 2013 ). Contrary to these findings, 32.5% of undergraduate students of a medical college in Delhi suffered from LBP at the time of survey ( Aggarwal et al, 2013 ), as well as 34.6% of students studying at health-related faculties at one university in Turkey ( Yucel & Torun, 2016 ). The prevalence of LBP was found to be the highest among medical students in Saudi Arabia: for example, the week prevalence of LBP among medical students ranged from 40.5% at university hospitals in Riyadh ( Algarni et al, 2017 ), to 52.5% among medical students of Jazan University ( Dighriri et al, 2019 ).…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…Compared to this study, 12-month prevalence of LBP was lower among the medical students in Pakistan (38.6%), 19 China (40.1%), 20 the US (42.8%), 21 Malaysia (46.1%), 22 India (47.5%), 10 Austria (53.4%), 14 Serbia (59.5%), 5 Brazil (59.9%), 23 Saudi Arabia (61.4%), 20 and was higher among the medical students in Turkey (96.4%). 34 The discrepancy in the LBP prevalence could be from some factors, including the variation of faculty year of study, academic curriculum, methodological heterogenicity, mode of data collection, cross-cultural factors, and subjective perception of pain. 35,36 Socio-demographic factors and LBP prevalence The findings of the study showed that sex and weight are two socio-demographic factors that were associated with 12-month prevalence of LBP among Bangladeshi medical students.…”
Section: Lbp Prevalencementioning
confidence: 99%